Belmour : a modern edition - Damer, Anne Seymour, 1748 or 1749-1828 (Northwestern world classics., 2011)
"Belmour chronicles the tangled romances of a group of eighteenth-century English aristocrats. The plot centers on charismatic Lord Belmour, a man of intense feeling and quick perception, who goes to great lengths to gain the affection of the lovely and mysterious Emily Melville, only to learn that she has recently married another man. His heartache propels him on an extensive journey across Europe, until fate ultimately leads their paths to cross once more. Set against vivid backdrops in Paris, Lisbon, Venice, and Rome, Belmour is a rich, multifaceted story of forbidden love and erotic intrigue that will appeal to those interested in the gothic romances of Ann Radcliffe and the psychological novels of Elizabeth Inchbald. Like her contemporary Jane Austen, Anne Damer casts a sharp and critical eye on the foibles of the aristocracy, yielding a memorable portrait of romantic love in the age of sensibility"--Back cover.